2015
DOI: 10.1007/s00774-015-0694-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D status and serum parathyroid hormone concentration and calcaneal stiffness in Japanese adolescents: sex differences in susceptibility to vitamin D deficiency

Abstract: There is currently insufficient information on serum 25-hydroxyvitamin D (25OHD) and parathyroid hormone (PTH) concentrations, and bone mineral status in healthy adolescents to allow reference values to be set. This study aimed to provide comparable data on vitamin D status in Japanese adolescents and to assess sex differences in susceptibility to vitamin D insufficiency. Serum 25OHD and PTH concentrations were measured in 1,380 healthy adolescents (aged 12-18 years). Subjects completed a questionnaire on exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
(69 reference statements)
2
22
0
Order By: Relevance
“…Similar results were observed in healthy individuals in Australia and Riga, and a value of 38 ng/mL was suggested as sufficient to avoid an increase in PTH [ 20 , 30 ]. Other studies reinforce the negative correlation between vitamin D and PTH [ 31 – 33 ].…”
Section: Discussionmentioning
confidence: 54%
“…Similar results were observed in healthy individuals in Australia and Riga, and a value of 38 ng/mL was suggested as sufficient to avoid an increase in PTH [ 20 , 30 ]. Other studies reinforce the negative correlation between vitamin D and PTH [ 31 – 33 ].…”
Section: Discussionmentioning
confidence: 54%
“…At least another Japanese study reported positive correlation between BMD and serum 25(OH)D level [14]. A recent study of 1,380 Japanese male and female teenagers between 12 and 18 years old reported positive correlations between serum 25(OH)D and calcaneal stiffness, which was significantly lower in those with serum 25(OH)D less than 20 ng/mL [19].…”
Section: ) Bone Mineral Density (Bmd)mentioning
confidence: 99%
“…In this study, the values in TS patients were even lower than in prior studies. The 25(OH)D values in Japanese population overall (approximately 16.7-18.1 ng/mL [17,18], and 18.7-21.2 ng/mL [19,20] in youths), are reportedly lower than those generally reported overseas. The fact that most of the patients in this study were Vitamin D deficient is considered a characteristic of TS as well as a racial/ethnic effect in the Japanese population.…”
Section: Discussionmentioning
confidence: 65%